Prevalence of Carotid Atheroma Plaque on Panoramic Imaging in Type II Diabetes Mellitus Patients: A Systematic Review - M Pavithra; Arvind Muthukrishnan (Wolters Kluwer Medknow Publications, 2023)
Background: Hyperglycemia and other risk factors lead to the formation of plaques in the neck area of the carotid artery. Carotid atheroma plaque may predispose or increase risk of cerebrovascular accident. Panoramic radiographs can pick up mere calcified plaque and early referral to a physician would prevent long-term complications. Materials and Methods: The electronic and hand search of studies published until October 2022, yielded a total of 17 articles, out of which 4 studies met the inclusion criteria. All studies examined the prevalence of carotid atheroma in panoramic images of patients with type 2 diabetes. The risk of bias was assessed by the Newcastle-Ottawa scale. Results: This systematic review search yielded 168 publications from various databases. After reading the full text, four articles were selected and met the selection criteria. All four studies showed the level of evidence IV which was assessed using Agency for Health Research and Quality (AHRO) guidelines. Conclusion: The prevalence of carotid atherosclerotic plaques is higher in diabetic patients compared to non-diabetic patients. Literature-based evidence suggests that carotid atheroma can be detected on panoramic images and the patients can be referred to a doctor for further examination and necessary treatment.